2015
DOI: 10.4236/pp.2015.65028
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Knowledge, Perception and Attitude towards Prescription Medicines Abuse among Medicines Prescribers and Dispensers in Nnewi Nigeria

Abstract: Background: Abuse of medicines is becoming a serious problem in many parts of the world, with negative consequences ranging from addiction, psychosis, cardiovascular complications, and premature deaths from unintentional overdose. Objectives: The objective of this study is to assess awareness, knowledge, perception and attitudes toward the abuse of prescription medicines (PM) among medicines prescribers and dispensers in Nigeria. Design and Participants: A descriptive cross-sectional study was carried out amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The regression analysis showed less likelihood of women who married early to receive antenatal care, four or more prenatal visits, iron supplementation and malaria preventive therapy during pregnancy but the adjusted odd ratio showed no significant association in both the frequency and quality of prenatal care received. The findings on poor prenatal care among early marriage generally agree with previous studies [7,20]. However, whereas many of the studies found significant association in the adjusted model between early marriage and low utilization of antenatal care, this study observed no difference.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The regression analysis showed less likelihood of women who married early to receive antenatal care, four or more prenatal visits, iron supplementation and malaria preventive therapy during pregnancy but the adjusted odd ratio showed no significant association in both the frequency and quality of prenatal care received. The findings on poor prenatal care among early marriage generally agree with previous studies [7,20]. However, whereas many of the studies found significant association in the adjusted model between early marriage and low utilization of antenatal care, this study observed no difference.…”
Section: Discussionsupporting
confidence: 90%
“…However, attaining four or more antenatal care visits has only been possible for fewer pregnant women particularly among adolescent women aged 15-19 years who are more likely to have comparatively lower access [3][4][5]. Nonetheless, uptake of both prenatal and intrapartum care has improved over the years, but progress has been slow and often constrained by many socio-economic factors such poverty, low educational status, geopolitical zone of residence, living in rural area [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation